التكامل المعرفي بين علم القراءات وعلم التفسير عند أبي عمرو الداني من خلال كتابه "المكتفى في الوقف والابتدا - بوحوش, غنية (جامعة الوادي university of eloued, 2023)
ملخص: أبو عمرو الداني عثمان بن سعيد، من كبار علماء الأندلس. له مكنة علمية بيّنة. ومؤلفات عديدة. اسم لامع في علوم القراءات القرآنية بأنواعها، غير أن له مشاركات في علوم شتى، وقد رام هذا المقال إظهار التكامل المعرفي عنده بين علمي القراءات والتفسير، من خلال كتابه "المكتفى في الوقف والابتدا". Abstract: Abu Amr al-Dani Othman bin Saeed, one of the great scholars of Andalusia. He has clear scientific mastery and numerous writings. He is a brilliant name in the sciences of Quranic readings of all kinds, however, he has contributions in various sciences. This article aims at showing his cognitive integration between the sciences of Quranic readings and tafsir in his book "Al-Muktafa fi Waqf wa Al-Ibtada
مقال
Keywords: التكامل المعرفي؛ ; القراءات؛ ; التفسير؛ ; أبو عمرو الداني؛ ; المكتفى في الوقف والابتدا